Predictors of Stroke Survivors’ Quality of Life During Home Rehabilitation: A Cross-Sectional Study - Sapang, Fransiska Anita Ekawati Rahayu; Baua, Maria Elizabeth; Sandi, Serlina (Nurse Media Journal of Nursing, 2025)
Background: Stroke survivors face the challenge of living in a body that functions differently than before, which impacts their quality of life. Stroke rehabilitation is essential, as the principle of neuroplasticity supports recovery from disability, and this process continues when survivors undergo home-based rehabilitation. However, the factors influencing their quality of life remain unclear.Purpose: This study aimed to investigate the predictors of stroke survivors’ quality of life during home rehabilitation.Methods: A cross-sectional study was conducted among 142 stroke survivors recruited using purposive sampling. Data were collected using the Stroke Survivor Quality of Life (SS-QOL) questionnaire and an additional questionnaire assessing knowledge, attitudes, and practices related to home rehabilitation. Logistic regression was employed to examine predictors of stroke survivors’ quality of life.Results: Most respondents (59.15%) were men, with a mean age of 59.25 years (SD = 10.5). Many stroke survivors had a high quality of life (n = 92; 64.79%), good knowledge (n = 114; 80.28%), positive attitudes (n = 83; 58.5%), and a high level of home rehabilitation practice (n = 89; 62.68%). Significant correlations were found between knowledge (p < 0.001), attitude (p = 0.040), and practice (p = 0.001) with stroke survivors’ quality of life.Conclusion: This study indicates significant correlations between knowledge, attitudes, and practices related to home rehabilitation and stroke survivors’ quality of life. These findings provide valuable insights for nurses, emphasizing the importance of structured health education on home-based rehabilitation to enhance stroke survivors’ quality of life.